Social determinants of health, inequalities, and public policies: actors for diabetic foot - Coto Ramírez, Diego; Rojas Bonilla, Jose María; Sáenz Madrigal, Rocío; Gómez Duarte, Ingrid; Miranda Loría, Gustavo (Horizonte Sanitario, 2024)
Objective: Analyze the related factors from the structural determinants, establish their intermediate determinants and determine precipitating risk factors in the study population.Materials and methods: Mixed research, collection of quantitative and qualitative data, with subsequent triangulation of data, with quantitative descriptive analysis of the database of the Diabetic Foot Clinic of the San Juan de Dios hospital of people hospitalized in the established period, and a semi-structured interview with thirty subjects with a history of hospitalization.Results: It was evident that the people most affected by diabetic foot are men between 50 and 59 years old, with illiteracy or incomplete primary school, with economic activities within the lowest quintiles, with a prevalence of psycho-affective disorder. They also have an absence of preventive actions by health establishments. The lack of a health education policy, unemployment and informality, lack of community participation, added to the demographic transition of Costa Rica, has a greater impact of this disease on the population.Conclusions: Social and economic conditions such as low schooling, gender, low income, unemployment and informality, poor support networks and lack of social participation negatively affect people with risk factors for suffering from Diabetes. In addition to the above, people do not receive comprehensive and integrated care, with poor self-care and little knowledge and empowerment about the disease, these are factors that allow people with Diabetes to have a higher risk of suffering from diabetic foot.Keywords: Social determinants of health, Mellitus diabetes, Diabetic foot, Public health.